Subband coding of high-fidelity quality audio signals - Tay, Sen Yong. (2009)
This project studies the method of Subband Coding as applied to high fidelity audio signals. A 32-band subband coder was built based on the MPEG's ISO 11172 draft specification. Polyphase Quadrature Filters were utilised in the implementation of the analysis and synthesis filter banks of the coder. Three different bit allocation schemes, two based on adaptive strategies and one on a non-adaptive strategy, were implemented for the Adaptive Forward Quantiser that was used to quantise the subbands before transmissions. Objective and subjective testings were performed to assess the performance of the coder with different quantisers. A study was made to extend the coder to cover a greater number of subbands and this resulted in the development of a new 64-band subband coder. Comparisons between the 32 and 64-band subband coders were then carried out.